The Perceptions of Undergraduate Students on Intercultural Communication in Universiti Sains Islam Malaysia (USIM). - Selvarani P. Kovil Pillai; Rosninawati Hussin (AJMC (Asian Journal of Media and Communication), 2017)
With the increase of globalization and migration, the study of intercultural communication has become more and more vital. The Ministry of Higher Education Malaysia has made a move to transform the landscape of tertiary education by intensifying internationalization and ensuring 10%-30% enrolment of international students in local universities and promoting the country as the education hub in the region. Taking the case study of the international students who are undergraduate students in Universiti Sains Islam Malaysia (USIM), this study focused on the intercultural communication aspect, the cultural barriers as well as the adaptation of these student in the new environment. The data was drawn from in-depth interviews conducted on the basis of the responses on 10 undergraduate students: four from Afghanistan, three from Nigeria, one each from Singapore, Indonesia, and Bangladesh. The findings showed issues facing by these students are not only about food and weather, but language, academic and finance systems and also feeling of alienation and discrimination.Keywords: perception, intercultural; communication; adjustment